Analisis Kepatuhan terhadap Regulasi PNS dan Implikasinya terhadap Budaya Kerja di Dinas Tenaga Kerja Sumatera Barat - Zahwa, Hadana; Syamsir; Asthy Perdana Putri; Ghea Febrina; Hanifah Tri Indah; Yola Nurfadhila; Devita Wulandari (Indo-MathEdu Intellectuals Journal, 2025)
This article examines the level of compliance of Civil Servants (Aparatur Sipil Negara/ASN) with regulations at the Manpower Office of West Sumatra Province and its implications for organizational work culture. The study aims to analyze the factors influencing ASN compliance and how such compliance contributes to the development of a professional, disciplined, and accountable work culture. A qualitative research method with a case study approach was employed, utilizing observations, in-depth interviews, and document analysis. The findings indicate that the level of ASN compliance is relatively high, particularly in terms of work discipline, which is supported by adequate understanding of regulations and the implementation of location-based attendance technology. Consistent enforcement of sanctions and exemplary leadership practices play a significant role in strengthening disciplinary values and accountability within the organizational culture. Nevertheless, several challenges were identified, including technical issues in the attendance system and individual behavioral differences among civil servants that affect the consistency of regulatory implementation. These findings confirm that civil servants' compliance is influenced not only by structural aspects such as regulations and monitoring systems, but also by the cultural dimension and organizational leadership. Therefore, strengthening adaptive monitoring systems, optimizing the use of technology, and enhancing the capacity and professional awareness of civil servants are important strategies to build a sustainable work culture.